From conception to COVID‐19: an arduous journey of tribulations of racism and triumphs - Daniell, Henry (Plant Biotechnol J, 2020)
Growing up in a densely wooded tropical forest enhanced my curiosity in plants and reading biography of Marie Curie profoundly influenced pursuit of my research career. Early in my career, I developed in vitro functional chloroplasts, capable of expressing foreign genes and this laid the foundation for the chloroplast genetic engineering field. Four decades of research has advanced chloroplast bioreactors for production of industrial enzymes or biopharmaceuticals by small or large companies. Because I experienced firsthand horrors of expensive vaccines or medicines, I devoted most of my career to develop affordable therapeutics. During this long journey, I suffered institutional racial discrimination but was rescued by several guardian angels. This biography gives readers a glimpse of tribulations and triumphs of my journey and recognizes important contributions made by my mentees.